2019
DOI: 10.5812/aapm.91207
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gabapentin on Postoperative Pain of Orthopedic Surgery of Lower Limb by Sciatic and Femoral Blockage in Children: A Clinical Trial

Abstract: BackgroundThere are meta-analyzes in adults demonstrating the benefits of using gabapentin to improve postoperative pain in orthopedic surgeries. In pediatrics, it has never been studied.ObjectivesThe aim of this study was to evaluate the use of gabapentin 10 mg/kg, orally, in postoperative analgesia, hemodynamic stability and its pre/postoperative anxiolytic effect in children subjected to unilateral inferior limb surgery.MethodsWe performed a double-blinded, randomized study. 84 patients in Albert Sabin Chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…They exert their analgesic effects by binding to the α-2-δ subunit of voltage-dependent calcium channels. Gabapentinoids may cause sedation, respiratory depression, and altered cognition, and they possess the potential for abuse (30)(31)(32)(33)(34)(35).…”
Section: Anticonvulsantsmentioning
confidence: 99%
“…They exert their analgesic effects by binding to the α-2-δ subunit of voltage-dependent calcium channels. Gabapentinoids may cause sedation, respiratory depression, and altered cognition, and they possess the potential for abuse (30)(31)(32)(33)(34)(35).…”
Section: Anticonvulsantsmentioning
confidence: 99%
“…So far, there have been studies on the effects of gabapentinoids, duloxetine, dexmedetomidine, ketamine, lidocaine, magnesium, and regional blocks (11)(12)(13)(14)(15)(16)(17). Despite the advances in pain management, opioids are still commonly used to treat these conditions (18).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past couple of decades, gabapentin has been studied as a potential alternative for the management of postoperative pain following a variety of surgeries. [8][9][10][11][12] Prior randomized controlled trials (RCTs) have found that perioperative gabapentin, given both preoperatively and postoperatively after thoracic, orthopedic, abdominal, genitourinary, otolaryngologic, limb, or breast surgeries, resulted in improved postoperative pain, reduced total postoperative opioid consumption, and diminished opioid-related adverse effects such as vomiting and pruritus. [8][9][10][11][12] For sinonasal procedures such as endoscopic sinus surgery (ESS) and septoplasty, prior RCTs have found that gabapentin administered preoperatively resulted in reduced pain levels and opioid consumption intraoperatively or immediately after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] Prior randomized controlled trials (RCTs) have found that perioperative gabapentin, given both preoperatively and postoperatively after thoracic, orthopedic, abdominal, genitourinary, otolaryngologic, limb, or breast surgeries, resulted in improved postoperative pain, reduced total postoperative opioid consumption, and diminished opioid-related adverse effects such as vomiting and pruritus. [8][9][10][11][12] For sinonasal procedures such as endoscopic sinus surgery (ESS) and septoplasty, prior RCTs have found that gabapentin administered preoperatively resulted in reduced pain levels and opioid consumption intraoperatively or immediately after surgery. [13][14][15][16][17] Most recently, a retrospective cohort study with 57 patients investigated the impact of preoperative gabapentin on postoperative pain control for 1 week after ESS and/or septoplasty.…”
Section: Introductionmentioning
confidence: 99%